Synthesis and Antibacterial Activity of 1,4-Quinoxaline Derivatives - A. Siddiqui, Anees; A. Khan, Suroor; Bhatt, Shibeer (Asian Journal of Chemistry, 2010)
1,4-Quinoxaline derivatives are synthesized by condensing o-phenylene diamine ard isatin. These are characterized on the basis of IR, NMR and mass spectral data. The final compounds were evaluated for antibacterial activity by taking Staphyloccus aureus as test organism.